196k views
3 votes
Help me please with question 4 b​

Help me please with question 4 b​-example-1

2 Answers

5 votes

Answer:

see explanation

Explanation:

The second term of sequence P is 2a + b

The third term of sequence Q is 3b + a

Equating gives

2a + b = 3b + a ( subtract a from both sides )

a + b = 3b ( subtract b from both sides )

a = 2b ← as required

User WayneSan
by
6.3k points
1 vote

Good evening ,

Explanation:

4 (b)

The 2nd term of sequence P is 2a+b

The 3rd term of sequence Q is 3b+a

2a+b=3b+a ⇌ (2a-a) = (3b-b) ⇌ a=2b.

:)

User Nicholas Mata
by
6.8k points